Military Chaplains and Religious Diversity - Hansen, Kim Philip. author. aut Link
XVI, 236 p.
Keywords: Based on extensive in-depth interviews with more than thirty active duty chaplains regarding their successes, failures and conflicts, the book is about the way military chaplains handle religious diversity among the enlisted they serve and within their own corps.